Discovery and exploration of widespread infection of mycoviruses in Phomopsis vexans, the causal agent of phomopsis blight of eggplant in China - Xie, Fang Ling; Zhou, Xin Yu; Xiao, Rong; Zhang, Chao Jun; Zhong, Jie; Zhou, Qian; Liu, Feng; Zhu, Hong Jian (Frontiers in Plant Science, 2022)
Phomopsis vexans, which causes Phomopsis blight of eggplant, has been reported worldwide. Mycoviruses are viruses that infect fungi. Among them, a part of mycoviruses can reduce the pathogenicity of their hosts known as hypovirulence. Therefore, fungal hypovirulence are potential biological agents to control fungal diseases. Furthermore discovering new mycoviruses will shed light on virus taxonomic evolution and virus-host interactions. 162 leaves and fruits samples of eggplant Phomopsis blight were collected from Hunan, Hubei, Jiangxi, Sichuan, Zhejiang, Fujian, Guangdong and Anhui Provinces during 2017 to 2019. 87 P. vexans strains were obtained from the 58 eggplant planting areas in eight provinces of China, which of them all infected by mycoviruses and mainly mixed infections. The genome of these viruses varies from 1-15kb. Five novel mycoviruses infecting P. vexans were obtained, including “Phomopsis vexans fusarivirus 1” (PvFV1), “Phomopsis vexans ourmia-like virus 1” (PvOLV1), “Phomopsis vexans endornavirus 2” (PvEV2), “Phomopsis vexans partitivirus 1” (PvPV1) and “Phomopsis vexans victorivirus L1” (PvVVL1). Thus, PvVVL1 has a unique genome structure and is the first report that the victorivirus consist of two segments. PvPV1 is the first report that Deltapartitivirus infect the fungus host.